Peran Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Karakter Peserta Didik Sekolah Dasar - Andriani, Eva; Saputro, Agung; Ma’ani, Arifatul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The teacher is the main figure who occupies a position and plays an important role in the world of education. Teachers are not only teachers of science, but also have to supervise to help the growth and development of students.